Awareness and Adoption of Recommended Technologies by Cassava Growers - A. Janaki Rani,; V. Palanisamy, (Journal of Agricultural Extension Management, 2025)
Cassava is an important tuber crop in India grown in 2.7 lakh hectares area and the production is 71 lakh tonnes. The average yield of cassava is 22 tonnes per hectare. Cassava is a rich source of starch (25 to 35 percent) mainly processed for starch and sago. In India, the major cassava growing states are Kerala and Tamil Nadu. Cassava is an industrial crop of Tamil Nadu and occupies 22082 ha of area with a production of 3797910 tons (Hort.Stat- 2006). The major traditional cassava growing districts are Salem, Namakkal, Erode, Cuddalore, Dharmapuri and Kaniyakumari mostly as rainfed. Among the Districts, Salem District stands first in area, production and productivity. The number of factories in Salem district alone is 650. It is estimated that 60 percent of the starch produced in India is from Salem district.